Antihistamine use during breastfeeding with focus on breast milk transfer and safety in humans: A systematic literature review. Issue 1 (26th October 2021) - Ngo, Elin; Spigset, Olav; Lupattelli, Angela; Panchaud, Alice; Annaert, Pieter; Allegaert, Karel; Nordeng, Hedvig
Abstract: Current data on use of antihistamines during breastfeeding and risks to the breastfed infant are insufficient. The aim of this systematic review was to provide an overview of studies measuring the levels of antihistamines in human breast milk, estimating the exposure for breastfed infants and/or reporting possible adverse effects on the breastfed infant. An additional aim was to review the antihistamine product labels available in the European Union (EU) and the United States. We searched seven online databases and identified seven human lactation studies that included 25 mother–infant pairs covering cetirizine, clemastine, ebastine, epinastine, loratadine, terfenadine and triprolidine. In addition, one study investigated the impact of chlorpheniramine or promethazine on prolactin levels among 17 women, and one study investigated possible adverse drug reactions in 85 breastfed infants exposed to various antihistamines. The relative infant dose was below 5% for all antihistamines, ranging from 0.3% for terfenadine to 4.5% for clemastine. Most product labels of the 10 antihistamines with available information in both the EU and the United States reported lack of evidence and recommended to avoid use during breastfeeding. The knowledge gap on antihistamines and lactation is extensive, and further human studies are warranted to ensure optimal treatment of breastfeeding women with allergy.